FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN DAN KOTA DI PROVINSI JAWA TENGAH 2018-2020 - Kiara Sabila Haque; Abdul Rohman (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of local revenue, capital expenditure, the size of the local government, and balancing funds on the financial performance of district and municipal governments in Central Java Province in 2018-2020. The independent variables used in this study are local revenue, capital expenditure, local government size and balancing funds, and the dependent variable is local government financial performance.The data used in this study is secondary data sourced from the Regional Government Financial Report and Audit Report which includes the APBD Realization Report and the Financial Statement Balance. The data was obtained from the BPK Representative of Central Java Province. This study uses multiple linear regression analysis on SPSS software.The results of the study show that local revenue does not affect the financial performance of local governments. Capital expenditures have a positive and significant effect on the financial performance of local governments. The size of the local government has a positive and significant effect on the financial performance of the local government. Balancing funds do not affect the financial performance of local governments.